JAMUR ENDOFITIK BS-1 DARI BUNGA SAMBILOTO (Andrographis paniculata) PADA MEDIA PERTUMBUHAN KACANG HIJAU: SKRINING FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN - Aisyah, Siti; Oktria, Wandi; Silvani, Mauline Adia; Riga, Riga (LPPM Akafarma Sunan Giri Ponorogo, 2024)
Sambiloto (Andrographis paniculata) is a medicinal plant in the Acanthaceae family. A. paniculata is known to synthesize active compounds with potent antioxidant properties that effectively hinder the activity of free radicals. Further studies of the antioxidant activity of this plant can be elaborated using its endophytic fungi. This research aims to analyze phytochemicals and measure the antioxidant activity (IC50) of the endophytic fungus BS-1 in flower of sambiloto. The results of the phytochemical screening of the ethyl acetate extract (EtOAc) of the BS-1 endophytic fungus were declared positive for containing steroid, terpenoid, phenolic and alkaloid compounds. The antioxidant test results indicated a very strong free radical inhibition ability with an IC50 value = 34.61 ppm.